To what extent are the pedagogical disciplines present in the degree courses of the health professions in Italy? Analysis of the presence of courses in the M-PED sectors in the study plans of the 2023/2024 cohort of the courses LM/SNT 02; 03; 04 - Avellino, Andrea (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
The master’s degree Courses in Health Professions (LM-SNT) have become part of the Italian university system only in recent decades and aim to train health professionals in the managerial, clinical and educa-tional fields. These three areas of training should also be developed in university curricula, but often the part relating to training (pedagogical and didactic) has a much lower presence than in the other areas. In this observational study, the extent to which the disciplines of the pedagogical scientific disciplinary sectors (M-PED/01; 02; 03; 04) are present in the planned study plans of the 2023/2024 cohort will be highlighted, also noting their weight in terms of credits and evaluating the academic position of the teachers to whom these courses are entrusted, where present. The data will help us to understand how marginal pedagogical and didactic training is in the curricula analysed.